STRATEGI KEBERLANJUTAN EKONOMI MASYARAKAT NELAYAN DI DESA MASADIAN KECAMATAN MENUI KEPULAUAN KABUPATEN MOROWALI - Amiludin, Hasrianti Amiludin; Sifatu, Wa Ode; Supiyah, Ratna (WELL-BEING: Journal of Social Welfare, 2021)
The purpose of this study was to determine the sustainability strategies for the economic livelihoods of indigenous people in Masadian Village, Menui District, Morowali Regency and strategies for increasing the economy of the puppet community in Desa Santas, Menadian District, Menow Islands, Morowali Regency. The results of the study showed that solving the problem of economic sustainability in the Desa Desa community uses an active strategy in which all communities express their daily needs by doing side jobs with various forms of work such as working as construction workers, ship / boatbuilders, fish buyers. The side jobs that are most chosen by fishermen are construction workers and shipbuilders and poverty reduction models with a participatory approach or the role of the wife / children to help the husband work